Marine Macroalgae: Prospective Hitchhikers of Ship Ballast - Temjensangba Imchen (Universitas Gadjah Mada, 2018)
Invasive alien species, on successful establishment, can displace native species. The threat of invasive species arises in view of their ability to outcompete and destabilize native biodiversity. Invasive species are found across all taxonomic groups of plants, animals and microorganisms. The green macroalga Ulva flexuosa has a potential to become invasive and this species was investigated for its hitchhiking potential under laboratory conditions. Zoospores of U. flexuosa were maintained at 4°C for nearly 10 months in the dark. Recruitment potential of zoospores after dark stress was tested in a modified Provasoli medium under optimal laboratoryconditions. The success rate of zoospore recruitment was 61%. The paper describes the transfer potential through shipping activities by correlating the Ulva zoospores recruitment potential and survivability.